2017
DOI: 10.3390/s17010137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ionospheric Scintillation Characteristics in Sub-Antarctica Region with GNSS Data at Macquarie Island

Abstract: Ionospheric scintillation has a great impact on radio propagation and electronic system performance, thus is extensively studied currently. The influence of scintillation on Global Navigation Satellite System (GNSS) is particularly evident, making GNSS an effective medium to study characteristics of scintillation. Ionospheric scintillation varies greatly in relation with temporal and spatial distribution. In this paper, both temporal and spatial characteristics of scintillation are investigated based on Macqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
2
7
0
Order By: Relevance
“…Severe loss of lock located between elevations 30° and 45° during the three years, where multipath effects on scintillation have been excluded. Similar calculations have done by Guo et al [ 30 ].…”
Section: Methodssupporting
confidence: 83%
“…Severe loss of lock located between elevations 30° and 45° during the three years, where multipath effects on scintillation have been excluded. Similar calculations have done by Guo et al [ 30 ].…”
Section: Methodssupporting
confidence: 83%
“…Previous work showed that strong geomagnetic and solar activities often trigger ionospheric disturbances (Guo et al, 2017;Moeketsi et al, 2007). To investigate the geomagnetic and solar environments during the study period, we examined four indices, including Kp, Dst, F10.7, and solar flare counts, as shown in Figure 2.…”
Section: Geomagnetic and Solar Conditionsmentioning
confidence: 99%
“…The influence of scintillation on global navigation satellite system (GNSS) is particularly evident, making GNSS an effective medium to study characteristics of scintillation. Ionospheric scintillation varies greatly in relation with temporal and spatial distribution [19].…”
Section: Methodsmentioning
confidence: 99%